2015
DOI: 10.1002/jmv.24121
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of a human G9P[4] rotavirus strain in Japan

Abstract: In a surveillance system in Osaka City, Japan, 48 sporadic rotavirus A (RVA) infections were detected during 2008/2009-2011/2012 seasons. The G/P-genotypes of detected RVAs were G1P[8], G2P[4], G3P[8], G9P[4], and G9P[8]. Although G9P[4] is a rare genotype that had not been reported in Japan, it was the second most prevalent genotype, following G1P[8], and accounted for 35.3% of RVA cases in the 2011/2012 season. Further genotyping revealed that the G9P[4] strain had genotype 2 internal protein genes except fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Regarding the variation in the prevalence of some uncommon genotypes (e.g., G9P[4] G9P[6], G3P[4], G3P[6]) detected after vaccine introduction in Mozambique, it is important to mention that a number of studies in Africa [ 16 , 25 , 32 ] and Asia (India and Japan) also reported these uncommon genotypes before vaccine introduction in low frequency [ 33 , 34 ]. These uncommon genotypes, apart from G9P[6], were also observed in Ireland before vaccine introduction [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the variation in the prevalence of some uncommon genotypes (e.g., G9P[4] G9P[6], G3P[4], G3P[6]) detected after vaccine introduction in Mozambique, it is important to mention that a number of studies in Africa [ 16 , 25 , 32 ] and Asia (India and Japan) also reported these uncommon genotypes before vaccine introduction in low frequency [ 33 , 34 ]. These uncommon genotypes, apart from G9P[6], were also observed in Ireland before vaccine introduction [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, surveillance studies conducted on RVAs reported a high prevalence of unusual G9P [4] rotavirus strains in many countries, such as Japan, Bangladesh, Paraguay and the Republic of Korea, and also including India [23,28,34,35]. Up to 2014, only two studies reported whole-genome analysis of G9P [4] RVA strains from countries such as Japan and the USA [36,37]. Subsequently, full-genome analysis of G9P [4] strains was also reported from eastern and western parts of India and Italy [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…A number of rotavirus surveillances conducted in several parts of Japan revealed that the prevalence of rotavirus A in pediatric patients in Japan was highly variable, ranging from 7.7% to 63.0% [Konno et al, ; Zhou et al, , ; Kitahori et al, , ; Phan et al, 2004, 2007a,b,c; Nakagomi et al, ; Yoshinaga et al, ; Dey et al, ; Harada et al, ; Nakagomi et al, ; Nakanishi et al, ; Ito et al, ; Kamiya et al, ; Chan‐it et al, ; Kawada et al, ; Kuzuya et al, ; Thongprachum et al, ; Yoneda et al, ; Thongprachum et al, ; Yamamoto et al, ], while rotavirus C was detected sporadically within the range of 0.1–6.8% [Kuzuya et al, ; Kuzuya et al, ; Thongprachum et al, ], as shown in Table . The rotavirus A was first reported in Japan in children hospitalized with diarrhea at considerable high prevalence of 63% [Konno et al, ].…”
Section: Gastroenteritis Virusesmentioning
confidence: 99%